DIMENSIONS OF COLLABORATION AND ACADEMIC PRODUCTIVITY IN SHARIA BANK LOYALTY RESEARCH: BIBLIOMETRIC ANALYSIS 2010 – 2024 - Cipta, Hendra; Hatamar, Hatamar; Ulfa, Khoirina (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
Customer loyalty to Islamic banks is one of the keys to sustainability for the Islamic banking industry, especially in strong competition facing conventional banks and financial technology (fintech) innovation. Nevertheless, literature regarding this topic has not been systematically mapped. Using a bibliometric approach, this study analyzes the publication trends, leading researchers, and collaboration patterns in Islamic bank customer loyalty studies. The Web of Science (WoS) is used to collect data and the keywords for customer loyalty and Islamic banks, and the time range of 2010 to 2024 is utilized for this study. Analysis using NVivo 12 and Voyant Tools (for network mapping and descriptive statistics) In the results of the study, 174 published documents were identified, where research articles predominated, a total of 156 articles. This publication trend has been on the rise, even peaking in 2023 with 30 publications. Indonesia and Malaysia stand out geographically as the leading contributors, mirroring the role of both countries as the strategic focal point of Islamic financial development. The most highly productive institutions are establishments such as Bandung State Polytechnic (Indonesia) and International Islamic University Malaysia (Malaysia). These findings offer an invaluable literature map so that further research and strategic ante-projects could be developed, of course with some added value for Islamic banking practitioners in its context of increasing customer loyalty. This study contributes to the academic knowledge with a bibliometric method, which is not widely used in the Islamic banking context.